Composite modelling of subaerial landslide-tsunamis in different water body geometries and novel insight into slide and wave kinematics - Heller, Valentin; Bruggemann, Mark; Spinneken, Johannes; Rogers, Benedict (Elsevier, 2016)
This article addresses subaerial landslide-tsunamis with a composite (experimental-numerical) modelling approach. A shortcoming of generic empirical equations used for hazard assessment is that they are commonly based on the two idealised water body geometries of a wave channel (2D) or a wave basin (3D). A recent systematic comparison of 2D and 3D physical block model tests revealed wave amplitude differences of up to a factor of 17. The present article investigates two of these recently presented 2D-3D test pairs in detail, involving a solitary-like wave (scenario 1) and Stokes-like waves (scenario 2). Results discussed include slide and water particle kinematics and novel pressure measurements on the slide front. Instantaneous slide-water interaction power graphs are derived and potential and kinetic wave energies are analysed. Solitary wave theory is found most appropriate to describe the wave kinematics associated with scenario 1, whereas Stokes theory accurately describes the tsunami in scenario 2. The data of both scenarios are further used to calibrate the smoothed particle hydrodynamics (SPH) code DualSPHysics v3.1, which includes a discrete element method (DEM)-based model to simulate the slide-ramp interaction. Five intermediate geometries, lying between the ideal 2D and 3D cases, are then investigated purely numerically. For a “channel” geometry with a diverging side wall angle of 7.5°, the wave amplitudes along the slide axes were found to lie approximately halfway between the values observed in 2D and 3D. At 45°, the amplitudes are practically identical to those in 3D. The study finally discusses the implications of the findings for engineering applications and illustrates the potential and current limitations of DualSPHysics for landslide-tsunami hazard assessment.